Integrative genomic and transcriptomic dissection of salt tolerance for Japonica rice improvement - Gao, Jingli; Kim, Tae-Heon; Baek, Dong-Hyun; Lee, Chang-Ju; Park, Woo-Geun; Yun, Sang Dae; Kim, Suk-Man (Frontiers in Plant Science, 2026)
Soil salinity is a major abiotic stress limiting rice productivity, particularly in coastal and irrigated regions. Japonica rice, widely cultivated in temperate regions, is moderately sensitive to salt stress, especially during the seedling stage. To accelerate salt-tolerance improvement in Japonica backgrounds, we conducted large-scale multi-environment phenotyping of 225 diverse rice cultivars under controlled salt stress (0.7% NaCl) across two seasons (spring and summer 2024), followed by genome-wide association study (GWAS) and transcriptome profiling. Best linear unbiased predictors (BLUPs) derived from linear mixed-effects models effectively corrected seasonal, spatial, and environmental variations, revealing substantial genotypic differences in seedling-stage salt tolerance. GWAS identified five novel QTLs (qSES3, qSES5, qSES6, qSES7, and qSES9), with qSES6 and qSES7 exhibiting strong synergistic effects. The transcriptome analysis of the highly tolerant cultivar ‘IR73571-3B-11-3-K2’ identified 834 DEGs, revealing enriched stress-responsive activities, such as oxidoreductase activity and phenylpropanoid biosynthesis. Integrating the GWAS and transcriptomic data highlighted Os07g0635500 (cytochrome P450) as a key candidate gene, and the haplotype analysis identifying two haplotypes, with Haplotype 2 conferring superior tolerance. However, favorable QTLs and haplotypes were predominantly found in Tongil-type cultivars, suggesting limited representation in Japonica cultivars. Therefore, targeted introgression and marker-assisted selection will be required to transfer salt tolerance traits into Japonica cultivars. Overall, this study dissected salt stress responses in rice and providing a multidimensional resource and practical insights for the molecular breeding of salt-tolerant Japonica rice.